Trait dimensionality and population choice alter estimates of phenotypic dissimilarity. Issue 7 (8th March 2017) - Carscadden, Kelly A.; Cadotte, Marc W.; Gilbert, Benjamin
Abstract: The ecological niche is a multi‐dimensional concept including aspects of resource use, environmental tolerance, and interspecific interactions, and the degree to which niches overlap is central to many ecological questions. Plant phenotypic traits are increasingly used as surrogates of species niches, but we lack an understanding of how key sampling decisions affect our ability to capture phenotypic differences among species. Using trait data of ecologically distinct monkeyflower ( Mimulus ) congeners, we employed linear discriminant analysis to determine how (1) dimensionality (the number and type of traits) and (2) variation within species influence how well measured traits reflect phenotypic differences among species. We conducted analyses using vegetative and floral traits in different combinations of up to 13 traits and compared the performance of commonly used functional traits such as specific leaf area against other morphological traits. We tested the importance of intraspecific variation by assessing how population choice changed our ability to discriminate species. Neither using key functional traits nor sampling across plant functions and organs maximized species discrimination. When using few traits, vegetative traits performed better than combinations of vegetative and floral traits or floral traits alone. Overall, including more traits increased our ability to detect phenotypic differences among species. Population choice and the number of traits used had comparable impacts on discriminating species. We addressed methodological challenges that have undermined cross‐study comparability of trait‐based approaches. Our results emphasize the importance of sampling among‐population trait variation and suggest that a high‐dimensional approach may best capture phenotypic variation among species with distinct niches. Abstract : We address key sampling issues in trait‐based ecology, demonstrating that measuring more traits and considering among‐population phenotypic variation may improve our understanding of species' phenotypic dissimilarity. Sampled monkeyflower species were no more distinctive when commonly used functional traits (vs. other morphological traits) were considered. To bridge current contrasting trait‐sampling approaches, we outline in which scenarios different strategies may be most useful.